Mass Eruption Rates of Tephra Plumes During the 2011–2015 Lava Fountain Paroxysms at Mt. Etna From Doppler Radar Retrievals - Freret-Lorgeril, Valentin; Donnadieu, Franck; Scollo, Simona; Provost, Ariel; Fréville, Patrick; Guéhenneux, Yannick; Hervier, Claude; Prestifilippo, Michele; Coltelli, Mauro (Frontiers in Earth Science, 2018)
Real-time estimation of eruptive source parameters during explosive volcanic eruptions is a major challenge in terms of hazard evaluation and risk assessment as these inputs are essential for tephra dispersal models to forecast the impact of ash plumes and tephra deposits. Between 2011 and 2015, Etna volcano has produced 49 paroxysms characterized by lava fountains generating tephra plumes that reached up to 15 km a.s.l.. We analyzed these paroxysms using the 23.5 cm wavelength Doppler radar (VOLDORAD 2B) signals along with visible camera images of the monitoring network of the Istituto Nazionale di Geofisica e Vulcanologia, Osservatorio Etneo. Range gating of the radar beam allows the identification of the active summit craters in real-time, no matter the meteorological conditions. The radar echoes help to mark (i) the onset of the paroxysm when unstable lava fountains, progressively taking over Strombolian activity, continuously supply the developing tephra plume, then (ii) the transition to stable fountains (climax), and (iii) the end of the climax with a waning phase, therefore providing paroxysm durations. We developed a new methodology to retrieve in real-time a Mass Eruption Rate (MER) proxy from the radar echo power and maximum Doppler velocity measured near the emission source. The increase in MER proxies is found to precede by several minutes the time variations of plume heights inferred from visible and X-Band radar imagery. A calibration of the MER proxy against ascent models based on observed plume heights leads to radar-derived climax MER from 2.96 × 104 to 3.26 × 106 kg s-1. The total erupted mass (TEM) of tephra was computed by integrating over beam volumes and paroxysm duration, allowing quantitative comparisons of the relative amounts of emitted tephra among the different paroxysms. When the climactic phase can be identified, it is found to frequently release 76% of the TEM. Calibrated TEMs are found to be larger than those retrieved by satellite and X-band radar observations, deposit analyses, ground-based infrared imagery or dispersion modeling. The radar-derived mass load parameters therefore represent a very powerful all-weather tool for the quantitative monitoring and real-time hazard assessment of tephra plumes at Etna.